Evaluation of the curative effect of Balanites aegyptiaca fruits ethanolic extract on Haemonchosis experimentally induced in Egyptian Baladi goats: phytoanalytical, parasitological and hematological studies - Jaheed, Ezatullah (J Parasit Dis, 2019)
This study aimed to screen phytochemical components and antioxidant activity of Balanites aegyptiaca ethanolic extract (BAF-EE) as well as to evaluate its curative effect on experimentally induced haemonchosis in goats. Phytochemical constitutes of BAF-EE were screened and identified using Gas Chromatography–mass Spectrometry (GC–MS) analysis and antioxidant effect was determined. Infective third larval stage (L3) of Haemonchus contortus (H. contortus) were obtained by culturing feces of goat harboring monospecific infection of the parasite. Twelve male goats were randomly divided into four groups (n = 3) as: G1 (infected—untreated) which served as control positive, G2 (infected—BAF-EE treated), G3 (infected-albendazole treated) and G4 (uninfected—BAF-EE treated) that served as control negative. Experimental infection was conducted with a single oral dose of 10,000 L3 at 0-time, whereas treatment with BAF-EE and albendazole were given at a single oral dose of 9 g and 5 mg/kg BW, respectively in the 5th week post infection (PI). Egg count per gram of feces (EPG) was conducted once a week and blood samples were drawn on zero time, 3rd week PI and then biweekly for 9 weeks, for conduction of hemogram. At the end of the experiment, all animals were slaughtered and adult worms in their abomasa were counted. GC–MS analysis confirmed 28 compounds in the extract which revealed presence of saponins, flavonoids, terpenoids, phenolics and alkaloids, and exhibited in vitro antioxidant activity. Clinical signs observed on the infected animals were signs of anemia, which were gradually disappeared post treatment (PT). A maximum reduction in EPG (88.10%) and worm burden (94.66%) was recorded on 4th week PT due to efficacy of BAF-EE in contrast to 98.29% and 96.95% efficacy of albendazole. All infected groups showed a significant decrease in hemoglobin (Hb) and packed cell volume (PCV) and presence of microcytic hypochromic anemia compared with G4. Goats treated with B. aegyptiaca and albendazole, exhibited significant increase in Hb and PCV 2 weeks PT and anemia changed to be normocytic hypochromic or microcytic normochromic in G2 and G3, respectively. Total white blood cells (WBCs) were elevated significantly in all infected groups which attributed to increase in lymphocytes, monocytes and eosinophils on expense of neutrophils. After treatments, WBCs and previously mentioned cells tended to decease. This study demonstrated that BAF-EE has anthelmintic effect against H. contortus and can improve hemogram and health condition of infected goats.